Pengaruh Pelatihan Pasar Modal, Kemajuan Teknologi dan Risiko Investasi Terhadap Minat Investasi di Pasar Modal - Wulan Rezky Amalya; Apriyani, Indah (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study aims to analyze the effect of capital market training, technological advances, and investment risk on the investment interest of FEB students in Bandar Lampung. The increasing number of capital market investors in Indonesia, particularly in Lampung, is influenced by several factors, including education, technological developments, and risk awareness. The research method employed a quantitative approach, utilizing snowball sampling to select 200 respondents. Primary data were collected through a Likert scale questionnaire and analyzed using multiple linear regression. The results indicate that capital market training positively influences investment interest, technological advances also have a positive effect, while investment risk negatively affects investment interest. These findings suggest that enhanced capital market education and training could foster greater investment interest, particularly among young people. Additionally, the role of technological advances in facilitating easier access to the capital market is significant, as it encourages investment participation. On the other hand, a lack of understanding of investment risks may deter students from investing, highlighting the need for better risk management education. The results provide valuable insights for academics, practitioners, and regulators to improve capital market education, leverage technology, and offer comprehensive risk management programs to encourage greater participation from young investors.